1995
DOI: 10.1164/ajrccm.152.5.7582313
|View full text |Cite
|
Sign up to set email alerts
|

Upper airway and soft tissue anatomy in normal subjects and patients with sleep-disordered breathing. Significance of the lateral pharyngeal walls.

Abstract: The geometry and caliber of the upper airway in apneic patients differs from those in normal subjects. The apneic airway is smaller and is narrowed laterally. Examination of the soft tissue structures surrounding the upper airway can lead to an understanding of these apneic airway dimensional changes. Magnetic resonance imaging was utilized to study the upper airway and surrounding soft tissue structures in 21 normal subjects, 21 snorer/mild apneic subjects, and 26 patients with obstructive sleep apnea. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
480
8
43

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 718 publications
(553 citation statements)
references
References 0 publications
22
480
8
43
Order By: Relevance
“…These alterations may accrue from adiposity around the pharynx and torso as follows. First, increases in neck circumference and fat deposited around the upper airway (12,72,(107)(108)(109) in obesity might narrow the upper airway. Second, upper airway collapsibility is higher in obese compared with nonobese individuals (25), and does not decrease appropriately when the pharynx is dilated by advancing the mandible anteriorly (110).…”
Section: Mechanical Effects Of Obesitymentioning
confidence: 99%
“…These alterations may accrue from adiposity around the pharynx and torso as follows. First, increases in neck circumference and fat deposited around the upper airway (12,72,(107)(108)(109) in obesity might narrow the upper airway. Second, upper airway collapsibility is higher in obese compared with nonobese individuals (25), and does not decrease appropriately when the pharynx is dilated by advancing the mandible anteriorly (110).…”
Section: Mechanical Effects Of Obesitymentioning
confidence: 99%
“…Schwab 34 proposed that the retropalatal region in patients with OSA was narrowed in the lateral aspect and the contrary, the retropalatal region in nonapneic people was narrowed in the AP dimension 34 . Li et al 20 reported that lateral narrowing of retropalatal region was closely associated with the degree of sleep apnea in their study 20 .…”
Section: Reported That 3dmentioning
confidence: 99%
“…Az OSAS előfordulási gyakorisága egyebekben szoros összefüggést mutat a dohányzással [7]. A kórkép kialakulásában jelentős szerepet játszanak bizonyos anatómiai eltérések [14]. A hormonális tényezők hatását a kórkép kialakulásának esélyére Reutrakul és mtsai vizsgálták egészséges várandós és nem várandós nő-kön.…”
unclassified